FDI in Russia in difficult times - Thomas Jost (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
The ongoing political crisis between Russia and the West jeopardize the achievements in economic relations that have been made over the past two decades. Foreign direct investments in Russia which are essential to modernize its economy may be lost if the Russian government does not send clear signals to restoreconfidence of Western investors.
Keywords: 330